Ecopedagogy Work for Planetary Sustainability: Ecopedagogical Teaching and Research in Diverse Local-to-Global Contexts - Misiaszek, Greg William; Mawa, Jannatul; Ensweiler, Michaela; Muganga, Allan (Ambiente & Educação: Revista de Educação Ambiental, 2026)
Trabalho ecopedagógico para a sustentabilidade planetária: ensino e pesquisa ecopedagógicos em diversos contextos do local ao global This article explores eleven teaching and research projects from diverse contexts that employ Freirean-based ecopedagogy and ecopedagogical literacies to foster students' praxis. Reinventing Freire’s work, ecopedagogy is founded on the inseparability of social violence and environmental destruction, aiming for "globally all-inclusive socio-environmental justice and planetary sustainability" (Misiaszek 2020). These projects illustrate key ecopedagogical principles: "world-Earth de-distancing", fostering a deep understanding of interconnectedness between humans and Earth; deepening and widening reflexivity, enabling critical analysis of local impacts and holistic planetary well-being; and utilizing (post)critical, problem-posing education that challenges dominant Northern epistemologies, neoliberal ideologies, and "wicked problems," while valuing diverse Indigenous and Southern knowledges. Collectively, these projects facilitate collective transformation and shared agency, moving beyond individual change towards systemic socio-environmental balance and ultimately achieving ecopedagogy's overall goal.